AUDITORÍA DE GESTIÓN A LA DIRECCIÓN ADMINISTRATIVA DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DE SOZORANGA, PERIODO 2017 - Gómez Lapo, Viviana Cecibel (2019)
Thesis work entitled "AUDIT OF MANAGEMENT TO THE ADMINISTRATIVE ADDRESS OF THE ADMINISTRATIVE GOVERNMENT DECENTRALIZED MUNICIPAL OF SOZORANGA, PERIOD 2017", was developed with the purpose of verifying and analyzing the efficiency, effectiveness and economy in achieving objectives and targets through the application of current legal regulations, as well as evaluate the internal control system implemented by the entity. The methodology used for its implementation is in accordance with the provisions of the Management Audit Manual issued by the Comptroller General of State, thus complying with the five phases: starting with the Preliminary Knowledge where a visit was made to the facilities of the municipality that allowed to have a general knowledge, regarding its constitution, organic structure, philosophical culture and the processes that the entity manages, to analyze its weaknesses; Planning analyzed the information provided by the entity that served as the basis for the control assessment for each subcomponent of the GAD Administrative Directorate such as the Human Talent, Public Procurement, Systems and Winery Unit and also the development of audit programmes. In the Implementation following the procedures established in the audit programmes, the control questionnaires were developed and applied to 5 inform the level of risk and the level of confidence of each of the sub-components examined, as well as the determination of significant findings that make it difficult to meet its proposed objectives and targets that were detailed in the narrative cards, and allowed for the obtaining of sufficient, competent and relevant evidence. Finally, the indicators of efficiency, efficiency and economy were applied; to determine the level of achievement of targets, objectives and the appropriate use of the resources held by the entity. The Results Communication issued a final audit report detailing the conclusions and recommendations that were determined after the Management Audit had been completed, which will allow officials to take action in order to optimize their resources and help achieve the objectives and goals. Finally, tracking leaves a schedule of compliance and implementation of recommendations established.